Factors influencing the prevalence of active trachoma in children aged one to nine years in Buyengo sub county Jinja district Uganda. A cross-sectional Study. - Ndikuno , Norman (Student's Journal of Health Research Africa, 2022)
Background: Trachoma Continues to be hyper-endemic in many rural areas of Uganda, Buyengo sub-county is one such area. It is an ancient Neglected Tropical Disease (NTD) which up to date is among the leading causes of avoidable blindness in the world. The disease is caused by the bacterium Chlamydia trachomatis. It is usually found in communities with poor hygiene and disappears spontaneously with the improving the socio-economic status of a community. Lifestyle and culture are known to influence the occurrence of trachoma and other eye diseases. Methodology: A descriptive cross-sectional study using both qualitative and quantitative methods was conducted in March 2016. Data was collected through face-to-face interviews, Observations, and examination of children eyes using structured questionnaires as guides. Results: Out of the 472 Children 6 (1.3%) were positive for active trachoma of these 1.3% had trachomatous follicular (TF) while 0% had trachomatous inflammation (TI) The children were found to washing their face without soap was 23.4 times more likely to get active trachoma as compared to those who used soap to wash their face (P<0.05) unclean faces were also 9.1 times more likely to lead children to acquire active trachoma (P<0.05). No availability of a pit latrine led to more chances of getting a trachoma infection (10 times) as compared to places where a latrine was available (P<0.05). Conclusion: The prevalence of active trachoma is low (1.3%) in the Buyengo sub-county with the following associated factors Unclean face of the child, Not washing the face with soap, not having a latrine, and availability of flies in the child’s face. Recommendation: There is a need for health workers to continue giving health education on the prevention of trachoma during village health talks, in outpatient departments, in the consultation room, and on radio talk shows.